Influence of the xanthan gum as a crosslinking agent on the physicochemical properties of chitosan microparticles containing green coffee extract. (October 2020) - Lawall Werneck Cerqueira, Ana Flávia; Protta Neiva, Giselle; Fernandes, Maria Fernanda; Leira Mota Conegundes, Jéssica; Stephani, Rodrigo; Cappa de Oliveira, Luiz Fernando; da Costa Ludwig, Zélia Maria; de Carvalho dos Anjos, Virgílio; Pinto Vilela, Fernanda Maria; Scio, Elita; Diniz Tavares, Guilherme; Pereira Rodarte, Mirian
Abstract: Chitosan (Ch) microparticles have been investigated for drug delivery through different administration routes, primarily oral. For this, synthetic crosslinking agents, such as sodium tripolyphosphate (TPP), are used to prepare these microparticles. In this sense, the objective of this study was to evaluate the potential of xanthan gum (XG) as a crosslinking agent aiming at the standardization of a natural polymer of low toxicity and low cost as an alternative to synthetic ones. The Ch-XG microparticles were prepared by the complex coacervation method and demonstrated high mucoadhesive capacity in vitro . Using green coffee extract, a phenolic-rich extract as a drug model, the microparticles crosslinked with XG showed satisfactory mean diameter (approximately 498 μm) and high entrapment efficiency (62.70 ± 5.20%.). Scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis proved the extract encapsulation in the polymeric matrix. Compared to conventional microparticles (Ch-TPP), Ch-XG microparticles provided a slower release of the 5-caffeoylquinic acid (5-CQA), in particular, in the simulated gastric fluid. Based on these findings, XG can be considered as a promising crosslinker for the preparation of chitosan microparticles, especially for oral drug delivery. Highlights: The chitosan/xanthan system demonstrated promising physicochemical properties. The chitosan/xanthan system demonstrated high mucoadhesive capacity. The xanthan gum acts as a promising crosslinker for chitosan microparticles. The natural system was efficient in microencapsulating the green coffee extract.